REPORT ON EXAMINATION OF RECORDS. (The Accounting Review, 1955)
The article presents the report on examination of records of the American Accounting Association by the Executive Committee. According to the report, the committee has examined the consolidated balance sheet of the association as of December 31, 1954 and the related statements of income and net worth of the General Fund and Life Membership Fund for the year then ended. The examination was made in accordance with generally accepted auditing standards and accordingly included such tests of the accounting records and such other auditing procedures as considered necessary in the circumstances. In the committee's opinion, the accompanying consolidated balance sheet and related statements of income and net worth present fairly the financial position of the American Accounting Association at December 31, 1954 and the results of its operations for the year then ended, in conformity with generally accepted principles of accounting applied on a basis consistent with that of the preceding year.